Referral and Diagnostic Trends in Children Attending the Child Psychology Clinic in a Tertiary Neurology Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Increasing numbers of parents are seeking services for concerns about their child's neurodevelopment due to better survival of high-risk newborns, rising literacy, and declining fertility rates.Objective: This study was aimed to investigate the referral and diagnostic pattern in children attending the child psychology clinic.Methodology: This retrospective study was carried out in the child psychology clinic of the National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from July 2019 to June 2021. Children up to 16 years of age attending the clinic during that study period were included. Data were retrieved from the clinic database and a semi-structured questionnaire was used to obtain sociodemographic, clinical information, causes of referral, the type of psychometric tests administered, and their interpretations.Results: Although a total of 1860 (4.16%) children were referred to the child psychology clinic from the outpatient department, 1460 (3.26%) children enrolled themselves in the clinic for evaluation. Their mean age was 6.24±2.56 years and the male to female ratio was 2.3:1. The majority (44.52%) of children were in the 0-5 year age group. Children having the features of Intellectual disability (24.66%), ASD (19.31%), ADHD (14.45%), and cerebral palsy (11.71%) were the most frequent causes of referral for psychological assessment. Epilepsy (6.23%), behavioral and emotional abnormality (4.38%), and speech delay (6.23%) also formed a major bulk. WISC-IV (30.04%), Conner's Rating Scale (22.31%), and DSM-V (15.45%) were the most frequent psychometric test applied in these groups of children. The most frequent diagnosis after the psychological assessment was cognitive delay followed by ADHD, ASD, and behavioral abnormality.Conclusion: A significant number of children is found to have disorders that has demanded psychological assessment and intervention.Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):3-8